Teaching Efficacy and Maladaptive Behavior in Preschool Settings: Efektivitas Pengajaran dan Perilaku Maladaptif di Lingkungan Pendidikan Anak Usia Dini - Moh Basirul Fuad; Widyastuti Widyastuti (Academia Open, 2025)
General Background: Preschool children are in a critical developmental phase where social and emotional regulation shape future adjustment. Specific Background: Maladaptive behavior in early childhood education settings may disrupt learning processes and social interaction, while teachers’ teaching efficacy reflects their confidence in managing classroom challenges. Knowledge Gap: Although teacher self-efficacy has been widely examined, limited empirical evidence specifically analyzes its relationship with maladaptive behavior among preschool children in Indonesian Islamic kindergarten contexts. Aims: This study aims to examine the relationship between teaching efficacy and maladaptive behavior in preschool children at KB/TK Aisyiyah in Sidoarjo. Results: Using a quantitative correlational design with 200 teachers, data were collected through the Teacher Sense of Efficacy Scale and the Strengths and Difficulties Questionnaire. Spearman’s rho analysis revealed a significant negative correlation (r = -0.201, p = 0.004), indicating that higher teaching efficacy is associated with lower maladaptive behavior, although the contribution was relatively small (4.6%). Novelty: The study provides empirical evidence linking teaching efficacy and maladaptive behavior within a specific preschool institutional network in Indonesia. Implications: Strengthening teacher efficacy through professional development programs may support better behavioral management and promote healthier classroom environments in early childhood education. Keywords: Teaching Efficacy, Maladaptive Behavior, Preschool Children, Early Childhood Education, Teacher Self-Efficacy Key Findings Highlights: Significant negative correlation identified between educator confidence and behavioral difficulties. Majority of participants demonstrated moderate levels across both measured constructs. Statistical contribution indicates limited yet meaningful association within classroom contexts.